Balanced Detection of 100-Gb/s Optical OFDM Signals With SSBI Cancellation Based on Fused-Type Fiber Mode-Selective Coupler - Ying Qiu; Ming Luo; Zhixue He; Xiang Li (IEEE Photonics Journal)
We propose a signal-to-signal beating interference (SSBI) cancellation scheme in two-mode fiber (TMF) transmission system based on balanced detection without requirement of a guard band. The SSBI can be eliminated based on the mode selectivity characteristic of mode coupler. The mode selectivity in mode coupler relies on the coupling behavior between the fundamental mode LP01 and the first-order mode LP11, which is highly dependent on the spatial orientation of the fiber modes. We design and fabricate a fused-type fiber mode coupler (FFMC) based on circular-core TMF. Based on the fabricated FFMC, we experimentally demonstrate a multi-band 100-Gb/s optical orthogonal frequency division multiplexing signal transmission over 10-m TMF with SSBI cancellation. Significant performance improvement is observed when compared with conventional direct detection scheme under the condition of insufficient bandwidth of a guard band.